2017
DOI: 10.1097/gme.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome and the risk of subsequent primary ovarian insufficiency: a nationwide population-based study

Abstract: As a possible precursor stage, prior PCOS is a significant and independent risk factor for development of POI. The use of metformin reduces the risk of POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…POI classification is based on the detection of signaling defects, autoimmunity, insufficient initial follicle number, genomic defects, and chemotherapy [ 23 ]. A previous report showed that POI incidence is higher among women with PCOS than in women without PCOS (3.73% vs. 0.44%) [ 24 ]. PCOS patients experience interruption of follicle development, resulting in the formation of cysts and eventually follicle depletion.…”
Section: Discussionmentioning
confidence: 99%
“…POI classification is based on the detection of signaling defects, autoimmunity, insufficient initial follicle number, genomic defects, and chemotherapy [ 23 ]. A previous report showed that POI incidence is higher among women with PCOS than in women without PCOS (3.73% vs. 0.44%) [ 24 ]. PCOS patients experience interruption of follicle development, resulting in the formation of cysts and eventually follicle depletion.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Since Rps26 was susceptibility to PCOS, and PCOS patients have higher risk for POF 38 . It seemed that our research mimics the process in which PCOS finally leads to POF.…”
Section: Discussionmentioning
confidence: 99%
“…выяснено, что частота встречаемости ПНЯ у лиц с СПКЯ составляет 3,73 % против 0,44 % у женщин без этой патологии. В связи с этим авторы предлагают рассматривать СПКЯ как начальную стадию развития ПНЯ [20].…”
Section: заболевания репродуктивной системы / Diseases Of the Reproductive Systemunclassified